6(x-1)=-14(x-5)

Simple and best practice solution for 6(x-1)=-14(x-5) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 6(x-1)=-14(x-5) equation:



6(x-1)=-14(x-5)
We move all terms to the left:
6(x-1)-(-14(x-5))=0
We multiply parentheses
6x-(-14(x-5))-6=0
We calculate terms in parentheses: -(-14(x-5)), so:
-14(x-5)
We multiply parentheses
-14x+70
Back to the equation:
-(-14x+70)
We get rid of parentheses
6x+14x-70-6=0
We add all the numbers together, and all the variables
20x-76=0
We move all terms containing x to the left, all other terms to the right
20x=76
x=76/20
x=3+4/5

See similar equations:

| 1/3m+3−5/6m=−15 | | 4y+7-10=10+3y | | (X^3-9)÷(x-3)=0 | | 2x+15=43-4x | | 4x+8=30+2x | | .75x=34 | | 4x2^5x=21 | | -4y=51+8 | | y/2+3=-18 | | 4A+8k=-268 | | (3n+2)n=5(n-4)*2n | | 8/9+y=5/9 | | 8h^2+9h-1224=0 | | 6y=25y+9 | | -10+7x=3x+2 | | 4(5x-9=-2(x+7) | | 6g/7=g+81 | | 0.666666(x-1)=11 | | .11=–d+15 | | 0=8h^2+9h-1224 | | 4x+1.8=9.4 | | x-(.25x)=34+x | | x-5+5=2x-11 | | m-4=-112 | | 12x/40=13 | | x-(.25x)=34=x | | 3=18+3(90-x) | | (d/3290)*5010=d | | 5x-3=-7x-147 | | 16n+7=-41 | | U^2+8u+3=0 | | 3|-10x+3|-2=67 |

Equations solver categories